Doing Time: The Experiences of Women Hospitalised for an Extended Time in Their Pregnancy - Lomax, Michele Jean (Auckland University of Technology, 2019)
Pregnancy and childbirth are regarded as physiological processes that usually follow a normal pathway to a positive outcome for mother and baby. For some women, this normal process is interrupted by a complication arising in their pregnancy causing the pregnancy to be reclassified as high-risk. A high-risk pregnancy often requires the woman to be hospitalised with bed rest, prescribed for varying amounts of time, until either the condition has resolved, or the baby is born safely. There has been some international research exploring the effects bed rest has on the physiological and psychological health of women. However, there are few studies, particularly in New Zealand, that explore the experiences of hospitalised women once they have safely birthed their baby and returned home. This hermeneutic phenomenological study aims to explore the experiences of women hospitalised for an extended time in their pregnancy, once they are discharged home. The expectation is to uncover any detrimental effects this may have had on the women’s postnatal well-being. Seven women from three District Health Boards in New Zealand were interviewed about their experience of being hospitalised for an extended time in their pregnancy. The women of this study were hospitalised for a period of between two and twelve weeks antenatally and from two days to two weeks postnatally. The women’s interviews were transcribed verbatim, written, read and re-read. van Manen’s (2016) methodological framework of the lifeworld existentials were used to analyse the data. Four themes emerged from this analysis: ‘feeling unsafe’, ‘feeling displaced’, ‘doing time-being imprisoned’, and ‘coming out the other side’. The findings of this thesis suggest that extended hospitalisation during pregnancy caused women to feel like prisoners with no control over their bodies, time, or decisions. These experiences had a long-term effect on the women’s mental well-being reaching into the postnatal period and beyond.
Keywords: High-risk pregnancy; Long-term hospitalisation; Phenomenology; Womens experience of pregnancy hospitalisation